Low tumour burden is associated with observation after surgery in patients with grade 2 astrocytoma and oligodendroglioma: results from the prospective multicentre LoG-Glio registry - Ziebart, Andreas; Onken, Julia Sophie; Nadji-Ohl, Minou; Jungk, Christine; rückriegel, Stefan; Wachter, Dorothee; Gerlach, Rüdiger; Forster, Marie-Thérèse; Roder, Constantin; Kniese, Katja; Neidert, Nicolas; Fabbrocini, Ludovica; et al. (Journal of neuro-oncology, 2025)
Recent evidence-based guidelines recommend adjuvant therapy following surgery for most patients with WHO grade 2 and 3 gliomas. However, deviations from these recommendations are frequently observed in clinical practice. This study aimed to evaluate patterns of postoperative management across Germany, using multicentre registry data from certified neuro-oncology centres.
Gesehen am 27.02.2026